Návrh optické sítě - Polaček, Adam (Vysoké učení technické v Brně. Fakulta elektrotechniky a komunikačních technologií, 2022)
Táto bakalárska práca sa zaoberá návrhu technologickej optickej siete pre oblasť Hradec Králové, pre spoločnosť ČEZD Distribuce. Teoretická časť práce, popisuje momentálne riešenie siete a rozoberá sieťové protokoly. Praktická časť práce popisuje pasívnu časť a logickú časť siete. Dôležitou časťou práce, je vláknová schéma a návrh konfigurácie pre smerovač a prepínač. V poslednej časti práce, je znázornená simulácia v programe GNS-3.

This bachelor thesis deals with the design of a technological optical network for the area of Hradec Králové, for the company ČEZD Distribuce. The theoretical part of the thesis describes the current network design and discusses network protocols. The practical part of the thesis describes the passive part and the logical part of the network. An important part of the thesis, is the fiber scheme and configuration design for router and switch. In the last part of the thesis, simulation in GNS-3 program is shown.
Optical network design
Keywords: Optika; vlákno; sieť; smerovač; prepínač; GNS–3; Optic; fibre; network; router; switch; GNS–3